Evaluation of gait outcomes for individuals with established unilateral transfemoral amputation following the provision of microprocessor controlled knees in the context of a clinical service. Issue 3 (June 2021) - Carse, Bruce; Scott, Helen; Brady, Laura; Colvin, John
Abstract : Background: Microprocessor controlled knees (MPKs) have been shown to improve gait outcomes for individuals with unilateral transfemoral amputation (TFA); however, previous studies have limitations, which may affect their applicability. Objectives: To compare gait outcomes between non-MPK and MPK conditions within a large and diverse cohort of established TFAs in the pragmatic context of an operational clinical service and to identify any demographic variables that correlate with changes in gait outcomes. Study Design: This is a retrospective cohort study. Methods: Full-body three-dimensional motion capture and a portable breath gas analyser were used to evaluate gait-specific outcomes both pre-MPK and 6 months post-MPK provisions in TFAs (n = 32). The primary outcome measure was gait profile score, along with the following secondary outcome measures: walking velocity, step length, step length symmetry ratio, step time symmetry ratio, vertical ground reaction force symmetry index, base of support, center of mass deviation, and oxygen cost of walking. Results: Data showed statistically significant improvement in gait profile score from 11.2° ± 2.2° to 10.1° ± 2.1° ( p < 0.01) between non-MPK and MPK conditions. Other outcomes which showed significant improvement were walking velocity ( p < 0.01), step length ( p < 0.01), vertical ground reaction force symmetry index ( p < 0.01), and center of mass deviation ( p < 0.05). Conclusions: MPK provision offered significant gait improvements to this cohort of TFAs in an operational clinical setting. There still remains a large gap in gait outcomes between this cohort and those of healthy unimpaired adults. Improvements in socket design, prosthetic foot design, and physiotherapy intervention could further reduce this gap.